Effect of Launaea taraxacifolia Leaf-based Diet on Enzymes and Biomarkers of Selected Tissues of High-fat Diet-Induced Hyperlipidemic Rats - Rukayat A. Oyegoke; Mopelola A. Ahmed-Hassan; Samuel T. Farohunbi; Omame John (AlQalam Journal of Medical and Applied Sciences, 2025)
The study investigated the effects of Launaea taraxacifolia leaf-based diet at 6.25% - 25% inclusion levels on selected enzymes and biomarkers of selected tissues of high-fat diet-induced hyperlipidemic rats. 36 female rats weighing 165.82 ± 2.10g were assigned to two groups: A (6) and B (30). Animals in group B were made hyperlipidemic by feeding on high-fat diet for six weeks and were later re-assigned into six groups as non-treated, atorvastatin-treated and Launaea taraxacifolia leaf-based diet-treated (6.25%, 12.5%, and 25% inclusion) and were maintained on their respective diets for six weeks. The activities/concentrations of enzymes/biomarkers in the selected tissues: liver (lactate dehydrogenase, alanine aspartate amino transferases, gamma glutamyl transferase), heart ( acid phosphatase, creatinine kinase), serum ( lactate dehydrogenase, alkaline and acid phosphatases, alanine, aspartate amino transferases, gamma glutamyl transferase, albumin, bilirubin, urea, uric acid and creatinine) were determined using standard methods. Results revealed that Launaea taraxacifolia-treated animals showed a significant reduction in serum creatinine, uric acid, urea, and serum protein, while a significant increase in creatinine kinase indicated a reduction in hyperlipidemic condition. Overall, the results from the study indicate that the leaves of Launaea taraxacifolia can reverse hyperlipidemia.